ESRA19-0199 Shoulder abduction weakness after erector spinae plane block; case report. (30th August 2019) - Cusack, R; Biancardi, B
Abstract : Background and aims: The erector spinae plane block is becoming increasingly popular as a method of anaesthesia, post-operative and emergency analgesia for a growing variety of limb and thoracic pathologies. The mechanism of action of anaesthesia in the erector spinae plane remains unclear. This block has gained popularity as it is more amenable to anaesthesiologists with less expertise and is reported to have fewer serious side effects than classic paravertebral block. As it becomes more prevalent in international practice, more potential side effects and adverse outcomes will guide the application of this technique. Methods: We present the case of a 62-year-old man who fell six feet onto solid ground and was admitted to hospital with multiple left sided rib fractures with a flail segment. Results: On admission to intensive care he was in type 1 respiratory failure as a result of his injuries. An erector spinae plane block with 0.375% levobupivacaine was performed at T5/6, with a good result. The following day the block was repeated with placement of a catheter and a 0.15% levobupivacaine infusion started at 10 ml/hr, which provided good analgesia. 24 hours later the patient reported significant left upper limb pain and was unable to abduct his shoulder against gravity. The catheter was retracted and the symptoms resolved. Conclusions: This represents a novel and previously undocumented adverse effect of local anaesthetic in the erector spinae plane. Every potential adverse effect must be considered by clinicians performing this block in their patients.